Concurrent dengue and typhoid infection: study from a tertiary care centre in Muzaffarnagar, India - Chauhan, Sapna; Sharma, Sachin; ., Surender; Singh, Paramjit (International Journal of Research in Medical Sciences, 2019)
Background: Acute febrile illness is a common presenting complaint during the rainy season. Rains predispose to both water and vector borne diseases. Co-infection of dengue with malaria, leptospirosis, typhoid, scrub typhus and other arboviral diseases can occur in endemic areas. Such dual infections are difficult to diagnose and create a diagnostic dilemma for the treating physician. Here in this study authors attempt to find out rates of concurrent dengue and typhoid infection. Methods: This retrospective study was done between August to November 2017. 403 patients presenting with acute febrile illness were studied. Diagnosis of dengue was done by rapid card test detecting NS1 antigen, IgM and IgG antibodies. Serodiagnosis of Salmonella infection was done by tube Widal test. Results: : Out of 403 febrile sera samples tested 154 (38.2%) were positive for dengue (either NS1 antigen or IgM antibodies or both), 71(17.6%) were positive for Widal test O and H titres ≥1:160) and 28 (6.9%) were positive for both dengue as well as Salmonella (Widal test). Conclusions: Acute febrile illnesses with diagnostic dilemma may be seen in cases of co-infection. Only better clinical judgement and right choice of laboratory tests can diagnose these diseases timely and prevent fatal outcomes.